Reputation for resolve : how leaders signal determination in international politics - Lupton, Danielle L., 1987- (Cornell studies in security affairs., 2020)
"Leaders establish reputations for resolve based on their statements and behavior, and these reputations critically influence the conduct of international diplomacy, especially during times of crisis"--